"Monitoring of Insecticide Resistance in Anopheles Sacharovi (Favre, 1903) in Borderline of Iran, Armenia, Naxcivan and Turkey, 2001" - Sh Salari Lak; H Vatandoost; MR Entezarmahdi; H Ashraf; MR Abai; M Nazari (Tehran University of Medical Sciences, 2002)
Malaria has recently been resurged in some parts of Iran which is bordered with Armenia, Naxcivan and Turkey. An attempt was made to asses the current status of insecticide resistance in the main malaria vector , An.sacharovi. Adult engorged mosquitoes were collected from dwellings during the seasonal activity of the vector, which is synchronized in summer 2001. Mosquitoes were subjected to the diagnostic dose of insecticides based on WHO method. Results showed that this species is still resistant to DDT, tolerant to dieldrin but susceptible to other insecticides such as, bendiocarb, propoxur, malathion, fenitothion, deltamethrin, permethrin, cyfluthrin, lambdacyhalothrin, and etofenprox with low frequency of tolerant gene in some population to some above mentioned insecticides.